Conservation & Consumption: A Study on the Crude Drug Trade in Threatened Medicinal Plants in Thiruvananthapuram District, Kerala. - Parvati Menon
The recent upswing in the popularity of herbal products and traditional systems of medicine is one of the major reasons for the depletion of medicinal plants in the wild; many species have become rare, endangered or even extinct. The rising demand for crude drugs in the market has also led to widespread adulteration of the plantbased crude drugs with dubious effect on the consumer. Also, an equitable share of monetary benefits from the trade do not reach the indigenous communities who live in forests who are the primary collectors of medicinal plants, which is a disincentive for the protection and preservation of the plants and its habitats. Various studies have identified certain plants as becoming rare and endangered in the wild. This study investigates certain aspects of the collection, trade and adulteration practices in such threatened ant-based crude drug trade in Thiruvananthapuram district, Kerala, India. The enquiry begins from the trade outlets; from the traders through suppliers to the collectors and to the sources of extraction so as to recommend conservation of such ecologically important areas; and also to identify other plant species that are reportedly becoming scarce. The instances of the prevalent drug adulteration practices are investigated. An effort has heen made to understand the pattern of price distribution of the trade with a view to learn the share earned by the collectors. Detailed interviews and field observations were conducted among the traders to get an overall idea of the medicinal plant trade in the district with focus on threatened species. The suppliers were traced and from them, the collectors. Extensive survey of f orest and non-forest land in the study area brought out data on major collection locations, species and their quantity. Adulteration of raw drug occurs at all stages, from collector to the retail trader. Major substitutes/adulterants were identified from samples collected and a list of original and substitute/adulterants was prepared. Medicinal plants have become scarce even in rural and suburban areas. The severely affected forest areas in the district were located. Field visits were made to the exact locations. Checklist of plants and estimates of extraction were prepared. It was found that several species other than the official list of threatened species were becoming scarce. It is recommended that population studies of such species should be undertaken to confirm their status in the wild. On the basis of quantity of extraction and habitats of threatened species, possible Germplasm conservation Areas in the forests of the study area were identified. Recommendations have been made for an equitable distribution of income through an improved retailing system and value-addition.